2019
DOI: 10.1002/cncr.32378
|View full text |Cite
|
Sign up to set email alerts
|

Race and delays in breast cancer treatment across the care continuum in the Carolina Breast Cancer Study

Abstract: Background After controlling for baseline disease factors, researchers have found that black women have worse breast cancer survival, and this suggests that treatment differences may contribute to poorer outcomes. Delays in initiating and completing treatment are one proposed mechanism. Methods Phase 3 of the Carolina Breast Cancer Study involved a large, population‐based cohort of women with incident breast cancer. For this analysis, we included black women (n = 1328) and white women (n = 1331) with stage I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 42 publications
1
40
3
2
Order By: Relevance
“…In fact, few studies have examined how characteristics of the health system affect racial differences in treatment. 51 We previously took initial steps toward addressing health care factors by assessing treatment delay by Area Health Education Center (AHEC) region, 27 and future work should capture more complex care-coordination variables such as distance to care, type of care center, and workload associated with treatment. 52 In conclusion, there are many dimensions of treatment delay, from diagnosis to treatment completion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, few studies have examined how characteristics of the health system affect racial differences in treatment. 51 We previously took initial steps toward addressing health care factors by assessing treatment delay by Area Health Education Center (AHEC) region, 27 and future work should capture more complex care-coordination variables such as distance to care, type of care center, and workload associated with treatment. 52 In conclusion, there are many dimensions of treatment delay, from diagnosis to treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Moreover, many studies have focused on delayed treatment initiation without considering other delays on the care continuum. 27 We have previously reported a more comprehensive approach to the definition and measurement of breast cancer treatment delays 27 and sought to apply this conceptualization of treatment delays in combination with latent class variables for SES and access to care. As reviewed by Palumbo et al, 28 latent class analysis (LCA) has distinct advantages compared with area-level SES and continuous measurements of SES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial/ethnic discrimination resulting from implicit bias has been shown to have significant impact on provider communication, patient perception of care, and health outcomes for persons of color. 30 32 While there is mixed evidence on the impact of healthcare provider implicit bias on health outcomes, 33 some studies have demonstrated the influence of healthcare provider implicit bias on clinical assessment, decision-making, and treatment recommendations for Black women 34 Implicit bias among healthcare providers has also been associated with lower quality of care. 35 All of these suggest that discrimination, whether explicit or implicit, contributes significantly to the health disparities that AA women continue to experience.…”
Section: Discussionmentioning
confidence: 99%
“…This would indicate two major conclusions: rst, our phenomenon of interest is no longer a real problem for them, and second, there has been a clear advancement in the management of women with breast cancer in high-income countries compared to low-and middle-income countries. However, recent studies conducted in these countries have shown inequalities in access to breast cancer diagnosis and care for vulnerable populations such as immigrant women, residents of rural areas and black individuals [62][63][64].…”
Section: Discussionmentioning
confidence: 99%